ANALISIS KOMPETENSI MENGAJAR GURU SERTIFIKASI (PROFESIONAL) SEBAGAI DASAR PENINGKATAN KOMPETENSI MENGAJAR GURU IPA PADA SMP NEGERI DI KABUPATEN ACEH BESAR - Juli Firmansyah; Dian Aswita; Syamsul Rizal (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2017)
The purpose of this study is to describe the performance of professional teachers (post-certification) after obtaining a certificate of professional educators as well as allowances. The main competencies of professional teachers can be assessed by 6 capabilities, including the ability to implement the lesson, create modules and instructional media, preparation of RPP, personal and social competence, liveliness in academic organization and academic achievement development capability. This study is a model study of the Goal-Free Evaluation Model. The study population is all teachers of SMP who have passed the certification in Aceh Besar District. Sampling is done purposive sampling to teachers of science lessons in Secondary Schools in Aceh Besar District. Headmaster Principals are also involved to assess teachers' performance on the aspects of instructional administration. Data were collected using questionnaire, then analyzed using quantitative and qualitative descriptive technique. The results showed from 6 Aspects of assessment, four aspects of them are learning ability, modules and learning media, preparation of RPP, personal and social competence have shown high performance. However two others namely liveliness in professional organizations and the development of academic achievement, still in low performance. Hopefully these results can be input for the Office of Education of Aceh Besar Regency as a basic material for improving the quality of education in terms of improving the performance of Professional Teachers in Aceh Besar Regency.